Economics and Education Financing: Literature Review - Jasmine, Khariza Arnita; Ulfah, Maria; Wicaksono, Luhur (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research analyzes the basic concept of education financing and how it impacts on improving the quality of education. This research uses book research methods. As education managers and stakeholders, the government and society have made various strategic efforts to achieve this. National education standards are one of the government's tasks. One of the eight national standards set by the National Education System Law Number 20 of 2003 is financing standards. Education financing is an important part of education management. Public awareness to bear the costs of education will essentially give the community the strength to be responsible for the provision of education. Implementation of PP no. 19 of 2005 has implications for the need to develop financing standards which include standardization of education cost components which include operational costs, investment costs and personal costs. In accordance with the amended 1945 Constitution, the Indonesian State has given the government a mandate to set the education budget at 20 percent of the state budget as stated in Article 31 Paragraph 4.